Comparison of some of reliability and Hazard estimation methods for Rayleigh logarithmic distribution using simulation with application - hameed, Alaa faris; Alwan, Iqbal Mahmoud (Journal of Economics and Administrative Sciences, 2020)
The question of estimation took a great interest in some engineering, statistical applications, various applied, human sciences, the methods provided by it helped to identify and accurately the many random processes. In this paper, methods were used through which the reliability function, risk function, and estimation of the distribution parameters were used, and the methods are (Moment Method, Maximum Likelihood Method), where an experimental study was conducted using a simulation method for the purpose of comparing the methods to show which of these methods are competent in practical application This is based on the observations generated from the Rayleigh logarithmic distribution (RL) with sample sizes (n = 30,70,100) and on the values ​​of different parameters. The comparison was made using the mean of the integral error squares (IMSE).